An unanticipated copy number variant of chromosome 15 disrupting SMAD3 reveals a three‐generation family at serious risk for aortic dissection. (21st August 2012) - Hilhorst‐Hofstee, Y; Scholte, AJHA; Rijlaarsdam, MEB; van, A; Kroft, LJ; Reijnierse, M; Ruivenkamp, CAL; Versteegh, MIM; Pals, G; Breuning, MH
<x xml:space="preserve">Abstract</x> Several genes involved in the familial appearance of thoracic aortic aneurysms and dissections (FTAAD) have been characterized recently, one of which is SMAD3. Mutations of SMAD3 cause a new syndromic form of aortic aneurysms and dissections associated with skeletal abnormalities. We discovered a small interstitial deletion of chromosome 15, leading to disruption of SMAD3, in a boy with mild mental retardation, behavioral problems and revealed features of the aneurysms‐osteoarthritis syndrome (AOS). Several family members carried the same deletion and showed features including aortic aneurysms and a dissection. This finding demonstrates that haploinsufficiency of SMAD3 leads to development of both thoracic aortic aneurysms and dissections, and the skeletal abnormalities that form part of the aneurysms‐osteoarthritis syndrome. Interestingly, the identification of this familial deletion is an example of an unanticipated result of a genomic microarray and led to the discovery of important but unrelated serious aortic disease in the proband and family members.